المعارضات الشعرية في شعر محمود سامي البارودي - فؤاد, أ.د. نيان نوشيروان; محمد, م. ئاوات باقي (Sulaimani Journal for Humanities, 2023)
The poetic oppositions in the poems of Mahmoud Sami Al-Baroudi are considered one of the most important pillars of building his poems, as a return to ancient Arabic literature and deriving meanings, contents, forms and words from the sources of power and prosperity in ancient Arabic literature and poetry. And that Al-Baroudi is fond of old words and meanings, and uses them for his poetic purpose, as he makes the poems of the ancients a poetic balance for his poems, and for this he opposed them and saw them and lived with their beautiful meanings. And his oppositions indicate his familiarity with the ancient times, and his full knowledge of the subtleties of his poets and their poems, and that his oppositions are clear of his command, and he did not come to him haphazardly, but rather he began to read them, memorize them, imitate them, and emulate them, and after his poetic fork became strong, he opposed them and competed with them as well.
Keywords: البارودي المعارضات الشعرية الشعر الجاهلي الشعر الإسلامي الشعر العباسي شعر العصور المتأخرة